Numerical solution of some spectral problems for the Stokes equations - Ivanchikov, A.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2003)
We consider a number of methods for computing the lower part of spectrum for the Stokes equations. The task is to find some minimal eigenvalues and corresponding eigenfunctions; when the eigensubspaces are many-dimensional, we construct a basis in each of them. The complete set of algorithms and several examples of numerical results obtained on rectangular domains are given.